Aspergillus niger biofilms for celulasas production: some structural and physiological aspects - Villena, Gretty K. (2003)
Aspergillus niger biofilms developed on polyester cloth were evaluated considering two aspects related to the growth on surfaces: structure and physiological behavior focused on cellulase production. The biofilm structure was assessed by using electron scanning microphotographs from inoculation and adsorption to 120 h growth. The microphotographs show that biofilm formation can be divided into three phases: 1) Adhesion, which is strongly increased by Aspergillus spore hydrophobicity; 2) Initial growth and development phase from spore germination, that begins 4 to 10 h after inoculation and continues up to 24 h when almost all available surface has been colonized; 3) Maturation phase in which biomass density is highly increased from 48 h after inoculation until 120 h growth when an internal channel organization that assures medium flow through biofilm is clearly evident as it is frequently reported for bacterial biofilms.Biofilm cellulolytic enzyme activity and productivity were also evaluated, being up to 40% and 55%, respectively, higher than that attained by freely suspended cultures. These results are in agreement with the behavior of most surface living microorganisms, which generally show a higher metabolic activity because of a differential gene expression. This work is a first attempt to understand the structure and physiology of industrial filamentous fungal biofilms as a response to the scarce available information in comparison with the vast and detailed information related to bacterial and pathogenic yeast biofilms.